A Study on Heat Transfer of Cu-Water Nanofluid in a 2D Inclined Porous Cavity using COMSOL Multiphysics - Abu, Nur Haidah Izzati; Muhamad Ghazali Kamardan, (Enhanced Knowledge in Sciences and Technology, 2024)
This study examined the heat transfer of Cu-water nanofluid in a 2D inclined porous cavity. The horizontal walls are perfectly insulated, and the vertical walls have different temperatures. The streamlines and isotherms were analyzed using COMSOL Multhiphysics. Darcy-Brinkman-Forchheimer equations have been modeled as transport equations for nanofluid-saturated porous mediums. The influence of non-dimensional parameters such as inclination angle was studied.  The results obtained reveal that the use of nanofluids is not important in the presence of strong internal heat generation.